2006
DOI: 10.1007/s10555-006-8161-9
|View full text |Cite
|
Sign up to set email alerts
|

A role for substance P in cancer promotion and progression: a mechanism to counteract intracellular death signals following oncogene activation or DNA damage

Abstract: In the present review we discuss a central role for substance P (SP) in carcinogenesis. We suggest that one mechanism to induce mitogenesis of tumor cells is the activation of neurokinin-1 receptor (NK1R) through SP, linking cancer promotion and progression to a neurokinin-mediated environment. After reviewing the role of both SP and its receptor NK1R in normal and neoplastic cells we propose the use of neurokinin-1 receptor antagonists as a novel and promising approach for treating patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
85
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 86 publications
10
85
0
4
Order By: Relevance
“…In addition, the findings of this study show that treatment of the three melanoma cell lines with this NK-1 receptor antagonist results in cell death and that such death occurs by apoptosis. This is in agreement with previous in vitro studies carried out in lung cancer, 35 rhabdomyosarcoma, 7 neuroblastoma, retinoblastoma, and larynx, gastric and colon carcinoma cell lines. [14][15][16]24 In a previous study, it has been reported that NK-1 receptors mediate shape changes in normal human embryonic kidney cells (HEK 293) and that these changes were prevented after preincubation with NK-1 receptor antagonists at 1 mM concentration.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Alsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the findings of this study show that treatment of the three melanoma cell lines with this NK-1 receptor antagonist results in cell death and that such death occurs by apoptosis. This is in agreement with previous in vitro studies carried out in lung cancer, 35 rhabdomyosarcoma, 7 neuroblastoma, retinoblastoma, and larynx, gastric and colon carcinoma cell lines. [14][15][16]24 In a previous study, it has been reported that NK-1 receptors mediate shape changes in normal human embryonic kidney cells (HEK 293) and that these changes were prevented after preincubation with NK-1 receptor antagonists at 1 mM concentration.…”
Section: Nk-1 Receptor and Aprepitant In Melanomas M Muñ Oz Et Alsupporting
confidence: 93%
“…4 In addition, the expression of SP has been reported in primary invasive malignant melanomas, metastatic melanomas, in situ melanomas, atypical (dysplastic) nevi, as well as spindle and epithelioid cell (Spitz) nevi, but was not detected in any acquired benign melanocytic nevi. 5 It has also been shown that activation of NK-1 receptors by SP induces mitogenesis in several melanoma cell lines 6,7 and others tumor cell lines. [8][9][10][11][12][13][14][15][16] SP is also a main mediator in the growth of capillary vessels in vivo and in the proliferation of cultured endothelial cells in vitro, and it has also been shown that NK-1 receptor agonists induced neoangiogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been proposed that a correlation exists between the expression rate of the NK1R/SP complex and prognosis in various types of cancer (18)(19)(20)(21)(22). Garcia-Recio et al identified that SP contributes to persistent transmodulation of the ErbB receptors, epidermal growth factor receptor (EGFR) and human epidermal growth factor 2 (HER2), in breast cancer, acting to enhance malignancy and therapeutic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this signature discriminates invasive and metastatic from localized HB and predicts prognosis with high accuracy (16). Additionally, it has recently been suggested that the expression of TACR1 may correlate with a clinically worse prognosis in some cancers (18)(19)(20)(21)(22). However, scientific evidence for such an association remains scarce.…”
Section: Introductionmentioning
confidence: 99%